Present status of research and production of tiger puffer Takifugu rubripes in Japan - Kikuchi, Kotaro (Facultad de Ciencias Biologicas, 2019)
The tiger puffer, Takifugu rubripes, is one of the most popular marine finfish cultured in Japan, and has a good market price of 3000JPY/kg that is three times higher than those for yellowtail and red sea bream. Although aquaculture production of tiger puffer hasbeen constant for the last 10 years at about 5000 tons a year, the market price has tended to decrease due to increasing imports ofpuffers, mostly from China. Tiger puffer has been produced with floating net cages along the coast of southern Japan like othermarine finfish species. One of the most serious problems of cage aquaculture is extremely low productivity due to high mortalityfrom outbreaks of parasitic diseases. Therefore, some farmers have started producing the fish in land based culture tanks withrunning seawater and some are interested in closed recirculating aquaculture. This paper describes the present status of commercialproduction of tiger puffer in Japan and available scientific information on optimum water temperature and salinity, proper stockingdensity, and nutrition and feeding for grow out. Productivity of tiger puffer in a closed system is also discussed.